Incomplete Contracting, Renegotiation, and Expectation-Based Loss Aversion - Fabian Herweg; Heiko Karle; Daniel Müller (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2014)
We consider a simple trading relationship between an expectation-based loss-averse buyer and profit-maximizing sellers. When writing a long-term contract the parties have to rely on renegotiations in order to ensure materially efficient trade ex post. The type of the concluded long-term contract affects the buyer's expectations regarding the outcome of renegotiation. If the buyer expects renegotiation always to take place, the parties are always able to implement the materially efficient good ex post. It can be optimal for the buyer, however, to expect that renegotiation does not take place. In this case, a good of too high quality or too low quality is traded ex post. Based on the buyer's expectation management, our theory provides a rationale for 'employment contracts' in the absence of non-contractible investments. Moreover, in an extension with non-contractible investments, we show that loss aversion can reduce the hold-up problem.
urn:nbn:de:bvb:19-epub-18389-9
Keywords: C78; D03; D86; 330; Behavioral Contract Theory; Expectation-Based Loss Aversion; Incomplete Contracts; Renegotiation